Are Word Problems Really More Difficult for Students with Low Language Proficiency? Investigating Percent Items in Different Formats and Types. Issue 3 (2017) - Pöhler, Birte; George, Ann Cathrice; Prediger, Susanne; Weinert, Henrike
No abstract available